OCCURRENCE OF DYSLIPIDEMIA IN NEWLY DIAGNOSED TYPE 2 DIABETES MELLITUS PATIENTS - 1Qamar Sajad 2Dr Zubair Ahmed 3Dr Aimen Saleem 4Dr Qudsia Usman 5Afan Shamim 6Dr Zofeen Aftab 7Kashif Lodhi (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
According to past research, the incidence of diabetes has increased by three times in both urban and rural regions, and in the near future, Pakistan will have a high number of diabetes patients. Due to alterations in lipid profiles, type 2 DM patients are more likely to develop vascular problems. Increased blood levels of triglycerides (TGs), total cholesterol (TC), or both, or decreased levels of elevated lipoprotein cholesterol are signs of diabetic dyslipidemia, which is more atherogenic (HDL-C). The risk of cardiovascular illnesses may be reduced by managing dyslipidemia.OBJECTIVE:  The aim of this research was to ascertain the occurrence of dyslipidemia in type-II diabetes mellitus patients who had just received their diagnosis.METHODS: the research was carried out at the Fatima Memorial Hospital Lahore. In the research, 100 people with type 2 diabetes who had just received a diagnosis were enrolled as cases, while 100 healthy people were included as controls. Both the control and cases groups' participants provided blood samples, which were then tested for fasting and post-meal plasma glucose, HDL-C, LDL-C, TG, TC, and HbA1c.RESULTS: Only 52% of controls were found to have dyslipidemia, compared to 84% of cases, and it was statistically significant that both the groups are different with p-value = 0.05.  In comparison to the controls, the cases had higher mean values for fasting and postprandial plasma glucose, HbA1c, LDL-C, TG, TC, and HbA1c (p0.05).CONCLUSIONS: This study demonstrated a favorable relationship between serum total cholesterol and glycemic parameters, LDL cholesterol, and triglycerides, and exhibited that dyslipidemia is frequent in recently diagnosed T2DM patients (p0.05). Since dyslipidemia is an established risk factor for cardiovascular illnesses, our research emphasizes the need and significance of taking action to reduce it in diabetes individuals.